Crisis communication: the case study of Kaspi bank of Kazakhstan (Herald of Journalism, 2023)
This article provides a certain insight into the crisis communication of Kaspi bank undertaken during a huge crisis situation in 2014.In 2014, the three banks of Kazakhstan: “Kaspi Bank”, “Bank Center Credit” and “Alliance bank” have simultaneously experienced a non-financial related crisis situation. This research study will examine crisis communication strategy of Kaspi Bank. Since, as compared to other banks, this bank has enacted a very effective and active crisis communication effort. It is believed, the crisis communication process undertaken by this bank has proved both effective and creative, which led the bank to overcome the crisis within three days, since they immediately created a crisis communication strategy, which was helpful in repairing their reputation and addressing the concerns of their stakeholders.The study first presents some general background information about the crisis situation, that the bank faced. Secondly, academic viewpoints and theories on crisis and crisis communication will be discussed. Thirdly, in the methodology part the qualitative and quantitative methods of study will be presented. Particularly, a crisis response strategies used by Kaspi bank during and after the crisis, the lexical choice of organization in its message creation, and representation of important actors and events in their crisis responses as based on the four crisis response materials that were explored via discourse analysis. Fourthly, findings of the research represented as a main part of the study. Finally, the reaction of stakeholders was investigated via comments on articles and news related to Kaspi Bank’s crisis situation. The findings displayed that the blaming crisis response strategy of Image Repair Theory, differentiation strategy of Apology Theory, denying crisis strategy of Situational Crisis Communication Theory on crisis communication were appropriate for Kaspi Bank to manage their crisis. This study is important, since there is limited research about crisis communication within bank sphere in Kazakhstan. That is why this single case study can shed light on the analysis of crisis communication strategies used in such situations, the effectiveness of their approaches to overcome the crisis, and the influence of communication on the public in the given context. In addition, this article is helpful for the researchers in communication and PR, as well as to students in this area.      Keywords: communication, crisis, crisis management, discourse analysis, content analysis.